Influence of Surface Treatment on The Mechanical and Viscoelastic Properties of Adhesive Joints Applied to The Oil and Gas Industry - Moraes, C. E. [UNESP]; Santos, L. F. P. [UNESP]; Leal, T. P. F. G.; Botelho, E. C.; Costa, M. L. [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2023)
Structural adhesives emerge as an alternative technique for joining materials used in tertiary structures in the oil and gas industry instead of welding, for example, in order to mitigate risks caused by the use of sparks on offshore platforms. Therefore, the present work aims to evaluate the influence of different surface treatments of the adherent material (carbon fiber/epoxy composite) on the mechanical behavior of the adhesive joints through the lap shear test. Furthermore, the viscoelastic properties of the epoxy-based structural adhesive were analyzed via dynamic-mechanical analysis (DMA). The results indicates that the adhesive exhibits residual curing when cured at room temperature and a post-curing process is required to increase its glass transition temperature (Tg) and its stiffness, Lap Shear tests results shows that the adherent surface treatment that generated the best mechanical response was cleaning with solvent, despite its lower roughness compared to the fuseply treatment, which indicates a strong correlation between roughness and wettability in obtaining resistant adhesive joints.
Keywords: Structural adhesives; Adhesive joints; Surface treatments; Viscoelastic properties